Bridging Size and Charge Effects of Mesoporous Silica Nanoparticles for Crossing the Blood–Brain Barrier - Chen, Yi-Ping; Chou, Chih-Ming; Chang, Tsu-Yuan; Ting, Hao; Dembélé, Julien; Chu, You-Tai; Liu, Tsang-Pai; Changou, Chun A.; Liu, Chien-Wei; Chen, Chien-Tsu (Frontiers in Chemistry, 2022)
The blood–brain barrier (BBB) is a highly selective cellular barrier that tightly controls the microenvironment of the central nervous system to restrict the passage of substances, which is a primary challenge in delivering therapeutic drugs to treat brain diseases. This study aimed to develop simple surface modifications of mesoporous silica nanoparticles (MSNs) without external stimuli or receptor protein conjugation, which exhibited a critical surface charge and size allowing them to cross the BBB. A series of MSNs with various charges and two different sizes of 50 and 200 nm were synthesized, which showed a uniform mesoporous structure with various surface zeta potentials ranging from +42.3 to −51.6 mV. Confocal microscopic results showed that 50 nm of strongly negatively charged N4-RMSN50@PEG/THPMP (∼−40 mV) could be significantly observed outside blood vessels of the brain in Tg(zfli1:EGFP) transgenic zebrafish embryos superior to the other negatively charged MSNs. However, very few positively charged MSNs were found in the brain, indicating that negatively charged MSNs could successfully penetrate the BBB. The data were confirmed by high-resolution images of 3D deconvoluted confocal microscopy and two-photon microscopy and zebrafish brain tissue sections. In addition, while increasing the size to 200 nm but maintaining the similar negative charge (∼40 mV), MSNs could not be detected in the brain of zebrafish, suggesting that transport across the BBB based on MSNs occurred in charge- and size-dependent manners. No obvious cytotoxicity was observed in the CTX-TNA2 astrocyte cell line and U87-MG glioma cell line treated with MSNs. After doxorubicin (Dox) loading, N4-RMSN50@PEG/THPMP/Dox enabled drug delivery and pH-responsive release. The toxicity assay showed that N4-RMSN50@PEG/THPMP could reduce Dox release, resulting in the increase of the survival rate in zebrafish. Flow cytometry demonstrated N4-RMSN50@PEG/THPMP had few cellular uptakes. Protein corona analysis revealed three transporter proteins, such as afamin, apolipoprotein E, and basigin, could contribute to BBB penetration, validating the possible mechanism of N4-RMSN50@PEG/THPMP crossing the BBB. With this simple approach, MSNs with critical negative charge and size could overcome the BBB-limiting characteristics of therapeutic drug molecules; furthermore, their use may also cause drug sustained-release in the brain, decreasing peripheral toxicity.